Effects of Surface Tension on the Stability of Surface Nanobubbles - Pan, Yongcai; He, Bing; Wen, Binghai (Frontiers in Physics, 2021)
The existence of surface nanobubbles has already been confirmed by variable detection methods, but the mechanism of their extraordinary stability remains unclear and has aroused widespread research interest in the past two decades. Experiments and theoretical analyses have tried to account for these stabilities such as the very long lifetime, very high pressure and very small contact angle. Attractive hydrophobic potential was applied to complement the pinning-oversaturation theory and successfully explain the survival of surface nanobubbles in undersaturation environment by some researchers. However, the survival of nanobubbles on hydrophilic surface still requires sizeable oversaturation. In this paper, we introduce the variable surface tensions, namely Tolman-dependence and state-dependence, and show that they effectively promote the stability of nanobubbles. The decrease in surface tension can lead to larger contact angle and even make the nanobubbles survivable on the highly hydrophilic surface. In Tolman-dependence, the changing rate in the contact angle evolution slows down, which is more obvious when the bubble size is close to the Tolman length. The contact angle is also getting larger in the state-dependence, and the increase of the gas saturation degree is beneficial to the stability of surface nanobubbles. With the gas saturation ratio of 3, the bubbles on the quite hydrophilic surface can also be stable, while grow up on the hydrophobic surface. The variable surface tensions weaken the need of saturation degree for the surface nanobubbles’ stability.